2022
DOI: 10.2991/aebmr.k.220104.016
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Hydroponics as a Home Industry

Abstract: This study aims to analyze the feasibility of a hydroponic business on a home industry scale. This research tries to respond to the rising hydroponic farming system, which allows it to be applied as an alternative to a home business. However, this development is not yet optimal for new entrepreneurs because the investment value is relatively high. Meanwhile, a business feasibility study is needed to justify that the high investment value is commensurate with the profitability generated from the hydroponic busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Results derived from the modified superstructure developed in this work are presented in Table 2. As it can be observed, several NPV values were negative, indicating that no benefits are being obtained or that they do not meet the expectations of the investment project [26] . For this reason, scenarios with a negative NPV will not be considered in the discussion.…”
Section: Resultsmentioning
confidence: 94%
“…Results derived from the modified superstructure developed in this work are presented in Table 2. As it can be observed, several NPV values were negative, indicating that no benefits are being obtained or that they do not meet the expectations of the investment project [26] . For this reason, scenarios with a negative NPV will not be considered in the discussion.…”
Section: Resultsmentioning
confidence: 94%
“…For example, in Brazil, a study showed that a hydroponic farm with 2475 m 2 of greenhouses was economically viable [97]. On a smaller scale, a feasibility study of a domestic industrial-scale hydroponic business (as an alternative home business) indicated excellent profitability [98]. Other studies revealed that domestic vertical hydroponic production may be economically viable, with the potential to increase food security and the sustainability of urban areas [99,100].…”
Section: Food System Sustainability Problem Home Hydroponics Solution...mentioning
confidence: 99%
“…Kemudian, setelah benih berkecambah dalam waktu seminggu, sayuran dipindahkan ke dalam pipa hidroponik yang telah diisi air dan nutrisi (Cifuentes-Torres et al, 2021;Idham et al, 2022;Sánchez et al, 2021;Shaik et al, 2022). Hidroponik memiliki potensi dan keuntungan finansial sebagai alternatif dalam skala home industry (Bumgarner & Hochmuth, 2019;Kholis et al, 2022).…”
Section: Pendahuluanunclassified